Oxaliplatin-Induced Peripheral Neuropathy and Identification of Unique Severity Groups in Colorectal Cancer - Griffith, Kathleen A. (J Pain Symptom Manage, 2017)
CONTEXT: Oxaliplatin-induced peripheral neuropathy (OIPN) is a dose limiting toxicity of oxaliplatin and affects most colorectal cancer (CRC) patients. OIPN is commonly evaluated by patient symptom report, using scales to reflect impairment. They do not discriminate between unique grouping of symptoms and signs, which impedes prompt identification of OIPN. OBJECTIVE: Our study objective was to identify clusters of symptoms and signs that differentiated underlying clinical severity and segregated patients within our population into OIPN subgroups. METHODS: Chemotherapy naïve CRC patients (N=148) receiving oxaliplatin were administered the Total Neuropathy Score clinical (TNSc(©)), which includes symptom report (sensory, motor, autonomic) and sensory examination (pin sense, vibration, reflexes). The TNSc(©) was administered prior to chemotherapy initiation (T0), and following cumulative doses of oxaliplatin 510-520 mg/m(2) (T1) and 1020-1040 mg/m(2) of oxaliplain (T2). Using mean T2 TNSc(©) scores, latent class analysis (LCA) grouped patients into OIPN severity cohorts. RESULTS: LCA categorized patients into 4 distinct OIPN groups: low symptoms and low signs (N=54); low symptoms and intermediate signs (n=44); low symptoms and high signs (n=21); and high symptoms and high signs (n=29). No differences were noted among OIPN groups on age, sex, chemotherapy regimen, or cumulative oxaliplatin dose. CONCLUSION: We identified OIPN patient groups with distinct symptoms/signs, demonstrating variability of OIPN presentation regardless of cumulative oxaliplatin dose. Over half of the sample had positive findings on OIPN examination despite little or no symptoms. Sensory examination of all patients receiving oxaliplatin is indicated for timely identification of OIPN, which will allow earlier symptom management.